2019
DOI: 10.3390/ijms20061344
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of the Metallothionein-1 Response by Cadmium-Exposed Normal Human Urothelial Cells

Abstract: Occupational and environmental exposure to cadmium is associated with the development of urothelial cancer. The metallothionein (MT) family of genes encodes proteins that sequester metal ions and modulate physiological processes, including zinc homeostasis. Little is known about the selectivity of expression of the different MT isoforms. Here, we examined the effect of cadmium exposure on MT gene and isoform expression by normal human urothelial (NHU) cell cultures. Baseline and cadmium-induced MT gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 101 publications
(124 reference statements)
2
11
0
Order By: Relevance
“…3A). This finding is in very good agreement with a previous report 64 in which MT1X, MT1A and MT1E levels were identified at 8.5%, 0.001% and 0.01% of MT2A levels (we found 2.5%, 0.015% and 0.021% respectively) and other studies in HeLa cells, 64 human urothelial cells 65 and various endothelial cells 66 showing that MT2A is the constitutively most strongly expressed MT form.…”
Section: Mt2a Protects Htr-8/svneo Cells From CD Toxicitysupporting
confidence: 93%
“…3A). This finding is in very good agreement with a previous report 64 in which MT1X, MT1A and MT1E levels were identified at 8.5%, 0.001% and 0.01% of MT2A levels (we found 2.5%, 0.015% and 0.021% respectively) and other studies in HeLa cells, 64 human urothelial cells 65 and various endothelial cells 66 showing that MT2A is the constitutively most strongly expressed MT form.…”
Section: Mt2a Protects Htr-8/svneo Cells From CD Toxicitysupporting
confidence: 93%
“…It is likely that the inconsistent responses to Zn supplementation or depletion, reflected by changes in the variable expression levels of ZIP1 and ZnT1, could be related to differences in Cd exposure among study subjects, given that Cd is a potent inducer of MT [48,49]. Furthermore, Cd and Zn are both found to be inducers of ZnT1 [22,50,51]. Overexpression of ZnT1 decreased intracellular zinc concentrations [25].…”
Section: Zinc (Cadmium) As a Concomitant Inducer Of Mt And Znt1mentioning
confidence: 99%
“…The antioxidant function of MTs protects the cells from free radicals and oxidative stress arising from mutagens, anticancer drugs, and radiation. The ability of MTs to bind Cd ++ , Hg ++ , Pt and other similar heavy metals protects cells from the toxicity of these metals (Krizkova et al, 2012;McNeill et al, 2019;Rahman et al, 2017;Wong and Stillman, 2018). On the other hand, it has been demonstrated that changes in MT expression could be associated with the process of carcinogenesis and 10 cancer progression (Krizkova et al, 2018;Si and Lang, 2018).…”
Section: Mts and Cancermentioning
confidence: 99%